Waveform measurement in mocrowave device characterization: impact on power amplifiers design - Quaglia, Roberto; Bell, James; Cripps, Steve; Tasker, Paul (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2016)
This paper describes an example of a measurement setup enabling waveform measurements during the load-pull characterization of a microwave power device. The significance of this measurement feature is highlighted showing how waveform engineering can be exploited to design high efficiency microwave power amplifiers.